Assessing the Degree of Development and Maturity of HR Systems: Suggested Criteria - Sweed, Dalia; Ashour, Ahmed (The Arab Journal of Administration, 2021)
The growing importance of intangible assets in modern organizations has led to increased interest in development of new mechanisms to evaluate HR systems. Recently, the literature introduced the concept of HR maturity, and several models have been developed to describe the gradual stages of this maturity. Despite the significant contribution of these models, they focused on assessing the HR maturity through the degree of HR-practices development as a key single criterion. The current study aimed at reviewing the literature of these models and trying to make a progress in this respect through suggesting new proposed criteria, to assess the HR maturity in a more comprehensive manner. The study presented seven proposed criteria: characteristics of HR manger, degree of horizontal alignment between HR practices, degree of vertical alignment between HR practices and corporate strategy, strategic role of HRM, the extent of organization reliance on external expert-institutions in the field of HR, the extent to which HR systems are reviewed and evaluated, and the degree to which HRM relies on IT. The present study suggested a classification to gradual levels of the proposed criteria. These criteria and classifications will contribute to develop the HR maturity concept, enrich the related models, and present a more comprehensive way to evaluate HR maturity in organizations.